2019
DOI: 10.1186/s12891-019-2855-y
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysmal bone cyst: results of an off label treatment with Denosumab

Abstract: Background: The treatment of aneurysmal bone cysts (ABCs) has evolved and less invasive methods have been tried. Denosumab is a monoclonal antibody which inhibits osteoclasts. It has been shown to be effective in giant cell tumour of bone (GCT) of bone and hence promises some effect also in ABC. We report on 6 patients treated with Denosumab and compare our results to the cases already published. Methods: Data of 6 patients with ABCs and patients whose treatment included Denosumab were retrospectively analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 45 publications
(53 reference statements)
1
55
0
17
Order By: Relevance
“…There are no data on real frequency of these sequelae. So far, there are only two case series reports of children with and without hypercalcemia after treatment [19,24]. An incidence of 22, respectively, 20% could be calculated, but, of course, the sample size is too small to generalize these data.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…There are no data on real frequency of these sequelae. So far, there are only two case series reports of children with and without hypercalcemia after treatment [19,24]. An incidence of 22, respectively, 20% could be calculated, but, of course, the sample size is too small to generalize these data.…”
Section: Discussionmentioning
confidence: 98%
“…Grasemann et al [13] found this side effect in a child with juvenile Paget, and Boyce et al [9] in a boy with severe fibrous dysplasia both treated with denosumab. Recently, Kurucu et al [19] and Dürr et al [24] reported reactive hypercalcemia in several denosumab-treated children and adolescents with aneurysmatic bone cysts, the phenomenon clearly must be related to the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 showed the speci c focus distribution. The content includes 16 cases of the study group and 10 cases of control group; the mean age for the patients of the 2 groups were 5.94 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) years old and 7.20…”
Section: General Datamentioning
confidence: 99%
“…The imaging of ABC shows that ABC is a polycystic and expansile osteolytic disorder, 70% of which are primary, and 30% are secondary. Up to now, the causes and pathogenic mechanisms of the ABC are still unknown, which leads to the diversi ed treatment methods of ABC [3][4]. Currently, the main treatment method of ABC is curettage and bone grafts with high-speed burring.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, denosumab has been used offlabel in adults with PHPT for the treatment of hypercalcemia prior to a parathyroidectomy [5, 6], long-term management of parathyroid carcinoma-mediated hypercalcemia [7-9], and medical treatment of osteoporosis in PHPT [10]. It has been used off-label in children with several skeletal diseases, for example, osteogenesis imperfecta [11][12][13], fibrous dysplasia [14], aneurysmal bone cysts [15][16][17][18], giant-cell tumors [19], Paget's disease of bone [20], glucocorticoid-induced osteoporosis in Duchenne muscular dystrophy [21], osteoradionecrosis [22], cherubism [18,23], as well as for hypercalcemia reduction after bone-marrow transplantation in osteopetrosis [24] and in squamous cell carcinoma [25]. To our knowledge, only 1 case of denosumab usage in a child with severe PHPT due to a parathyroid carcinoma and ineffectiveness of bisphosphonates has been reported to date [26].…”
Section: Introductionmentioning
confidence: 99%